GINA 2020: what's new and why?. (3rd October 2021) - Ish, Pranav; Malhotra, Nipun; Gupta, Nitesh
Abstract: The Global initiative against asthma (GINA) 2020 strategy has been released with some changes and updates. GINA recommends the continuation of medications, avoidance of nebulization and spirometry, and ensuring a written asthma action plan in COVID-19 times. GINA 2020 specifies which step of management is to be followed according to the patient's symptoms in an easy flowchart. Clinicians need to be aware of the changes and the evidence behind them.